PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN (Studi Kasus di Food Court Mall Karawang Central Plaza) - Raden Raditio Wratsongko; Mochamad Afrizal Maulana (Jurnal Pijar, 2026)
This study aims to determine and analyze the influence of Service Quality and Price on Consumer Satisfaction. The research method is quantitative using secondary data. The population used is a case study at the Karawang Central Plaza Mall Food Court. The sampling technique used was purposive sampling, with a sample of 106 respondents. Based on statistical analysis methods, the indicators in this study are valid and reliable, the data are normally distributed, there is no multicollinearity, and there is no heteroscedasticity. The results and discussion indicate that Service Quality has a significant effect on Consumer Satisfaction, and Price has a significant effect on Consumer Satisfaction. Simultaneously, Service Quality and Price influence Consumer Satisfaction. Keywords: Service Quality, Price, Consumer Satisfaction